Grindability Features of Torrefied Biomass - Mateusz Tymoszuk; Joanna Wnorowska; Sylwester Kalisz (Energies)
Economic and legal conditions of the European power industry enforce higher participation of biomass in the thermal energy mix per power unit, due to the necessity of carbon dioxide emission reduction. One of the most important features dictating the suitability of biomass fuel for utilization in pulverized fuel-fired boilers is its grindability. The grindability of biomass is a difficult parameter to estimate due to its non-uniform morphology and inhomogeneous character. Milling and co-milling of large amounts of biomass can deteriorate the mill output and make it difficult to ensure the proper particle size distribution of the pulverized fuel fed into the combustion chamber. The main objective was to determine whether torrefaction pre-treatments could increase the grindability features of various types of biomass. Investigations of raw and torrefied biomass grindability were performed with the use of a modified Hardgrove Index for alder chips, palm kernel shells, and willow chips. Additionally, semi-industrial scale milling tests were performed, which allowed for the evaluation of torrefied biomass suitability for continuous grinding installations equipped with vertical spindle mills. According to the analysis, an increase in the biomass grindability index after the torrefaction process was shown. Additionally, it was noted that for milling low-density materials (e.g., torrefied biomass), changes in the construction of the industrial mill classifier may be necessary for the proper grinding circuit operation.